Pengaruh Model Project Baset Learning dengan Pemanfaatan Video Terhadap Kemampuan Berpikir Kreatif dan Hasil Belajar IPAS Siswa SD - Aminah, Siti Aminah; Dwi Setyowati , Nur Aini (Jurnal Pendidikan (Teori dan Praktik), 2024)
This research aims to analyze the significant differences in the Project Based Learning model with the use of videos and conventional learning in terms of creative thinking abilities and student learning outcomes, as well as analyzing the significant differences in increasing creative thinking abilities and students' science learning outcomes before and after being treated with the Project Based Learning model with use of video. The research method uses a quantitative type of experiment, Quasi Experimental Nonequivalent Control Group Design Pretest-Posttest. The research population was all students in class V (five) at Al Ikhlas Islamic Elementary School, Cipete, totaling 109 students. The results of the research show that there are significant differences in creative thinking abilities and student learning outcomes between those using the Project Based Learning model and those using videos using conventional learning. There was a significant increase in students' creative thinking abilities and IPAS learning outcomes after being treated with the application of the Project Based Learning model using different videos before being treated with the application of the Project Based Learning model using videos. In general, there is a positive and significant effect (2 tailed) 0.002 < 0.05 of the application of the Project Based Learning model with the use of videos on the creative thinking abilities and science learning outcomes of elementary school students.